PENDEKATAN GURU DAN KOLABORASI DENGAN ORANG TUA SERTA PERAN PSIKOLOG DALAM MENGIKUTSERTAKAN ANAK BERKEBUTUHAN KHUSUS DI KELAS REGULAR UNTUK SISWA SEKOLAH DASAR - Nanda Oktavia; Huqqat Inayatul Khairi; Eka Yuanda Putri; Septi Fitri Meilana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to understand teachers' challenges and strategies in dealing with students with special needs in inclusive schools. The method used was an interview with a teacher who has experience teaching inclusive classes in public schools. The main problems encountered include variations in students' special needs, such as cognitive, emotional and behavioral disorders. Teachers also face obstacles in collaboration with parents who are less than optimal in providing support at home. Interviews showed that teachers adjusted the curriculum based on the abilities of students with disabilities, focusing on basic skills such as reading, writing and counting and independence. Interactive learning media such as videos are used to improve student focus. Collaboration between teachers, parents and professionals is recognized as important in supporting student development, although implementation is not always optimal. In addition, students with disabilities are integrated with regular students by providing modified Learner Worksheets (LKPD) as needed. In conclusion, inclusive learning requires curriculum adaptation, interactive learning media and close collaboration between teachers, parents and professionals to overcome the learning difficulties of students with disabilities and ensure they can develop to their potential.